2009
DOI: 10.1103/physreve.80.011902
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting desynchronization in rat hippocampal slice induced by coordinated reset stimulation

Abstract: In computational models it has been shown that appropriate stimulation protocols may reshape the connectivity pattern of neural or oscillator networks with synaptic plasticity in a way that the network learns or unlearns strong synchronization. The underlying mechanism is that a network is shifted from one attractor to another, so that long-lasting stimulation effects are caused which persist after the cessation of stimulation. Here we study long-lasting effects of multisite electrical stimulation in a rat hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 34 publications
3
75
0
Order By: Relevance
“…However, very small samples (corresponding to low grid point resolutions) resulted in chance electrode configurations, since the spatial extent of the samples was sparse relative to the spatial features of the electric field. The algorithm presented here also allows for fast computation of multiple stimulating electrode configurations using the same DBSA to target different neuronal subpopulations within a target region, as in the case of coordinated reset stimulation [64], [65] to desynchronize pathological oscillations.…”
Section: Discussionmentioning
confidence: 99%
“…However, very small samples (corresponding to low grid point resolutions) resulted in chance electrode configurations, since the spatial extent of the samples was sparse relative to the spatial features of the electric field. The algorithm presented here also allows for fast computation of multiple stimulating electrode configurations using the same DBSA to target different neuronal subpopulations within a target region, as in the case of coordinated reset stimulation [64], [65] to desynchronize pathological oscillations.…”
Section: Discussionmentioning
confidence: 99%
“…From the experimental and clinical studies, it is known that a safe extracellular electrical stimulation can be several orders of magnitude larger (ranging up to a few volts) than the natural voltage (some tens of millivolts) of the neurons [27,37]. The stimulation current of an effective CR stimulation or patterned pulse-train stimulation is in the above range [13,15]. We therefore expect that the considered stimulation strength will not violate the safety requirements for clinical applications.…”
Section: Neuronal Network Activationmentioning
confidence: 99%
“…To exploit this synaptic plasticity effect of DBS, Tass and colleagues have proposed a coordinated reset (CR) stimulation, which is a short-duration desynchronizing stimulation protocol that leads to a therapeutic synaptic reshaping of neuronal networks [208]. In epileptic hippocampal slices of a rat it was shown that the CR-stimulation has long-lasting desynchronizing effects [209].…”
Section: Introductionmentioning
confidence: 99%